Edukasi Kesehatan Dan Deteksi Dini Diabetes Melitus Dan Hipertensi Di Kelurahan Batu Ceper - Shieva Nur Azizah Ahmad (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Hypertension and diabetes mellitus are big challenges in Indonesia. These two diseases are most often found in health services with a fairly high prevalence. It is important to carry out early detection of diabetes mellitus and hypertension in order to optimize management if detected and the public also needs to be given education to understand the importance of checking health status. This service activity was carried out in 2 (two) stages, namely the first stage of health counseling for diabetes mellitus and hypertension, then followed by checking blood pressure and checking blood sugar for local residents to determine the blood pressure and blood sugar of residents who had attended the counseling event. In the first stage, the method is lecture, discussion and question and answer. Community service activities regarding health education (counseling) about hypertension and diabetes mellitus received enthusiastic responses from residents. Similar activities should be carried out continuously to increase public knowledge, especially regarding non-communicable diseases. Activities can be in the form of ongoing counseling to all residents.